Designing and implementation of law in managing outermost small islands in North Sulawesi Province - Karwur, Denny B. A (AQUATIC SCIENCE & MANAGEMENT, 2013)
Small islands bordering a region have tremendous potential in supporting national development. The determination of management policy is very important, because the existence of marine resources is a strategic border issue. The islands in the border regions of the country are vulnerable to the intervention of other countries, and transnational crime. The concept of development policies of small islands in Indonesia must be planned and implemented in an integrated manner for the development and welfare of the national state of Indonesia. The northern region of Indonesia is bordering the Philippines. Here North Sulawesi Province is important for the integrity of the management of small islands and border areas of coastal law enforcement Indonesia. Element target, and strategies of delimitation Exclusive Economic Zone in particular, between Indonesia and the Philippines states that overlap to optimize the management of natural resources. Draft Law on Small Islands State Border and the provision of local government authority to carry out the duty of assistance border management. Stating Small Islands in the border region as the island state and issued a special certificate© Pulau-pulau kecil di wilayah perbatasan memiliki potensi yang luar biasa dalam mendukung pembangunan nasional. Penentuan kebijakan pengelolaan sangat penting, karena keberadaan (eksistensi) sumberdaya laut di perbatasan yang strategis. Pulau-pulau di wilayah perbatasan negara rentan terhadap intervensi negara-negara lain, dan kejahatan transnasional. Konsep kebijakan pembangunan pulau-pulau kecil di Indonesia harus direncanakan dan dilaksanakan secara terpadu untuk pengembangan dan kesejahteraan negara dan bangsa Indonesia. Wilayah Indonesia bagian utara yang berbatasan dengan negara Filipina. Provinsi Sulawesi Utara, penting bagi integritas pengelolaan pulau-pulau kecil dan daerah perbatasan bagi penegakan hukum pesisir Indonesia. Elemen target, dan strategi adalah penetapan batas (delimitasi) Zona Ekonomi Eksklusif pada khususnya, antara Indonesia dan Filipina menyatakan bahwa terjadi tumpang tindih, untuk mengoptimalkan pengelolaan sumberdaya alam. RUU tentang Pulau-pulau Kecil Perbatasan Negara dan pemberian kewenangan bagi pemerintah daerah untuk melaksanakan tugas perbantuan pengelolaan perbatasan. Menyatakan Pulau-Pulau Kecil di wilayah perbatasan sebagai bagian pulau negara dan mengeluarkan sertifikat khusus©